Hepatitis serology predicts tumor and liver-disease characteristics but not prognosis after resection of hepatocellular carcinoma - Abdalla, Eddie (2004)
The impact of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection on survival rates after resection of hepatocellular carcinoma (HCC) is controversial. The objective of this study was to determine whether serologic evidence of HBV or HCV infection ("hepatitis serology") can predict underlying liver disease, tumor factors, and survival rates in patients with HCC. Using a multicenter international database, we identified 446 patients with complete HBV and HCV serology. One hundred twenty-six patients were negative for HBV and HCV, 163 patients had HBV infection only, 79 patients had HCV infection only, and 78 patients had coinfection with HBV and HCV. Patients with hepatitis were more likely to have tumors smaller than 5 cm and bilateral HCC involvement. Hepatitis status (negative vs. HBV vs. HCV vs. coinfection with HBV and HCV) did not predict tumor grade or the presence of multiple tumor nodules. Patients with HCV or coinfection with HBV and HCV exhibited a lower incidence of vascular invasion, but worse fibrosis than patients with negative serology or HBV. The median survival rate was 47.9 months. The presence of hepatitis did not significantly affect the survival rate, but hepatic fibrosis and vascular invasion predicted a decreased survival rate. The prognosis after resection of HCC is influenced by tumor factors and liver disease, but not by HBV or HCV infection. The treatment for HCC should be dictated by the extent of underlying liver disease rather than by hepatitis serology.